(untitled) (International Journal of Physiotherapy, 2017)
Background: The Alzheimer’s disease is the most common form of dementia and represents 60% of its cases. The disease is characterized by cognitive, non-cognitive and functional deficits and it’s incurable. The main of this study was to examine the effects of the aerobic exercise in combination with the music therapy and memory exercises in functional and cognitive ability on a patient with that have been affected by middle type (Second stage) of Alzheimer’s disease. Methods: Thirty patients from Chronic Diseases Center, with Alzheimer’s disease, divided between an intervention and a control group, participated in this randomized controlled study. (Thirty patients with Alzheimer’s were chosen from chronic disease center, and are divided into an intervention and a control group). The intervention requires 30 minutes of aerobic exercise, 10 minutes of memory games and music therapy, three times a week, for the duration of 12 weeks. The outcome measures the “Mini Mental State Examination” (MMSE) scale and the “Alzheimer’s Disease Assessment Scale cognitive test” (ADAS) for the cognitive ability, “Katz Index Independence in Activities of Daily Living” (ADL), “Get up and Go test” and “One leg standing balance test” (OLST) for the functionality. A three-way analysis of variance designs was applied to compare changes in each outcome measure before and after the intervention between the groups. Results: The MMSE score decrease significantly for the control group (males: 16.00 ± 4.04 to 15.14 ± 4.01 and for females: 16.00 ± 1.85 to 15.25 ± 1.98 before and after intervention) but not for the intervention group (p > 0.05) (males: 16.25 ± 2.71 to 16.12 ± 2.94 and females: 12.85 ± 2.67 to 12.57 ± 2.93). The ADAS score on intervention experimental therapy group was significantly low (males: 39.00 ± 7.98 to 37.50 ± 8.12 and females: 49.85 ± 6.54 to 48.28 ± 6.79). In the Get up and Go test (males: 18.87 ± 5.24 to 17.87 ± 4.15 and females: 19.85 ± 4.94 to 18.57 ± 4.64) and in the OLST(males: 4.57 ± 3.10 to 6.00 ± 2.77 and females: 4.00 ± 3.26 to 5.28 ± 3.40) there was a sign of progress in the results, while in the ADL no difference was observed in any group. (experimental group males: 3.50 ± 1.19 to 3.50 ± 1.19 and females: 2.57 ± 1.13 to 2.57 ± 1.13, control group males: 3.57 ± 1.51 to 3.57 ± 1.51 and females: 3.50 ± 0.75 to 3.50 ± 0.75). Conclusion: The aerobic exercise combined with the music therapy and the memory tests offer some improvement in cognitive and functional ability and contribute to the deteriorating delay of the symptoms of patients that suffer from Alzheimer and are hospitalized.